Comparative analysis of the variability of the human leukocyte antigen peptide‐binding pockets in patients with acute leukaemia. (20th October 2022) - Boukouaci, Wahid; Rivera‐Franco, Monica M.; Volt, Fernanda; Wu, Ching‐Lien; Rafii, Hanadi; Cappelli, Barbara; Scigliuolo, Graziana Maria; Kenzey, Chantal; Ruggeri, Annalisa; Rocha, Vanderson; Gluckman, Eliane; Tamouza, Ryad
Summary: The association between acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML) and the human leukocyte antigens (HLA) has rarely been studied in terms of diversity of peptide‐binding pockets. The objective of this study was to analyse whether motifs of HLA class I and class II peptide‐binding pockets and/or their amino acid positions were differentially associated with ALL and AML. We included 849 patients from the Eurocord/European Blood and Marrow Transplant registry. The HLA peptide‐binding pockets whose amino acid variability was analysed were B and F for HLA class I, P4, P6, and P9 for HLA‐DRB1, and P4 and P9 for HLA‐DQB1. The motif RFDRAY in P4 of HLA‐DRB1*16:01/02/03/05 alleles and the motif YYVSY in P9 of HLA‐DQB1*05:02/04/05 alleles, were statistically associated with ALL (corrected p value [ p c ] = 0.001 and p c = 0.035 respectively). The frequency of serine 57 in the P9 of HLA‐DQB1 was higher in ALL (odds ratio 2.09, 95% confidence interval: 1.27–3.44; p c = 0.037). Our analysis suggests that specific motifs in terms of HLA class II pockets and amino acids might be unique to ALL. The associations identified in this study encourage further investigation oF the role of HLA peptide‐binding pockets and their amino acids in immune processes underpinning acute leukaemia and ultimately in immunotherapy settings.